Differentiation of Cold Tolerance in an Artificial Population of a Mangrove Species, Kandelia obovata, Is Associated With Geographic Origins - Lu, Wen-Xun; Zhang, Bing-Huang; Zhang, Yuan-Ye; Yang, Sheng-Chang (Frontiers in Plant Science, 2022)
The geographic distribution of a plant species often has an adaptative meaning. Temperature is one of the climatic factors that may shape the geographic and genetic structures of plant populations. Mangroves are temperature-sensitive plants and their distributions are severely limited by low temperatures. It is unknown, however, to what extent temperature contributes to their population differentiation and evolution. Kandelia obovata is a mangrove species with high cold tolerance in the Northern Hemisphere. We investigated the phenotypic responses of the artificial population of K. obovata with plants transplanted from different source populations to extremely low temperatures in the Yueqing County (28º20′N), Zhejiang Province of China, during winters of 2015–2016.Within this artificial population, three phenotypic groups with different cold-resistant abilities were defined. We assessed the genetic diversity and structure of these phenotypic groups as well as five natural populations along a latitude gradient using 10 nuclear and 6 plastid microsatellite markers. The association analysis of the cold-resistant capability and the genetic constitution of the phenotypic groups/natural populations revealed that different phenotypic groups had different genetic underpinnings. Our study results suggested that low temperature plays a crucial role in promoting population differentiation during the long-term adaptive evolution of K. obovata. This may provide instructive information to the forest industry for afforestation.